2016
DOI: 10.3767/003158516x691212
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary history of the sequestrate genus Rossbeevera (Boletaceae) reveals a new genus Turmalinea and highlights the utility of ITS minisatellite-like insertions for molecular identification

Abstract: The sequestrate (truffle-like) basidiomycete genera Rossbeevera, Chamonixia, and Octaviania are closely related to the epigeous mushroom genera Leccinum and Leccinellum. In order to elucidate the properties and placement of several undescribed sequestrate taxa in the group and to reveal the evolutionary history of Rossbeevera and its allies, we conducted phylogenetic analyses based on three nuclear (ITS, nLSU, EF-1α) and two mitochondrial DNA loci (ATP6 and mtSSU) as well as precise morphological observations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 86 publications
(121 reference statements)
0
29
0
Order By: Relevance
“…Introgression and incomplete lineage sorting have been documented in other Leccinoideae genera, namely Rossbeevera T. Lebel et al and Turmalinea Orihara & N. Maek., and may have been overlooked in other groups (Orihara et al 2016). However, this kind of phenomenon, although problematic in species identification and phylogenetic analysis should not commonly result in false-positives in mgDNA species delimitation (i.e., wrongly considering divergent sequences as belonging to different species), except in the case of incomplete concerted evolution of the ITS sequences.…”
Section: Case Studies From Basidiomycotamentioning
confidence: 99%
“…Introgression and incomplete lineage sorting have been documented in other Leccinoideae genera, namely Rossbeevera T. Lebel et al and Turmalinea Orihara & N. Maek., and may have been overlooked in other groups (Orihara et al 2016). However, this kind of phenomenon, although problematic in species identification and phylogenetic analysis should not commonly result in false-positives in mgDNA species delimitation (i.e., wrongly considering divergent sequences as belonging to different species), except in the case of incomplete concerted evolution of the ITS sequences.…”
Section: Case Studies From Basidiomycotamentioning
confidence: 99%
“…in New Zealand, the diverse truffle flora is mostly epigeal). Further, although the majority of sequestrate fungi in Australia appears to have transitioned locally, Octaviania and Rossbeevera, two sequestrate genera of Boletaceae, were already sequestrate when they arrived in Australia from Asia (Orihara et al 2016). Therefore, conditions in Australia did not influence their sequestration, but must have been conducive to the establishment of these species following their dispersal.…”
Section: Historical Climatic Effects On Sequestration Of Agaricomycetmentioning
confidence: 99%
“…As far as we know, however, the present study is the rst case that demonstrated interspeci c hybridization in sequestrate basidiomycetes based on molecular evidence. Given the multiple traces of introgression among intraspeci c lineages shown by Orihara et al (2016a) and the interspeci c hybridization within Octaviania discussed here, it appears that the sequestrate genera in the Leccinoideae may be less reproductively isolated when the two lineages have been ecologically isolated (e.g. there is therefore no need for reproductive isolation to reinforce species boundaries).…”
Section: Discussionmentioning
confidence: 91%